PREVALENCE OF GASTROINTESTINAL NEMATODE INFECTION IN SOWS ON VARIOUS PIG BREEDING FARMS IN GIANYAR DISTRICT, BALI - I Wayan Mahesa Satria Paramananda; Ida Bagus Made Oka; Nyoman Adi Suratma; I Putu Cahyadi Putra (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Gastrointestinal nematode infections in sows can cause physiological decline in pigs, fetal development problems, and reduced milk production. This study aimed to determine the prevalence of gastrointestinal nematode infections in sows during the gestation, lactation, and dry phases at a pig breeding farm in Gianyar District, Bali, Indonesia. This was a cross-sectional study using purposive sampling. A total of 204 fecal samples from sows in the gestation, lactation, and dry phases, collected from seven sub-districts in Gianyar Regency, were used in this study. Fecal samples were examined using sedimentation and flotation concentration methods with saturated salt to identify nematode eggs. Prevalence data were described descriptively, while the chi-square test was used to determine the relationship between the prevalence of gastrointestinal nematode infections in pregnant, lactating, and dry sows. The study reported a nematode prevalence of 46.56%, consisting of Strongyl-type worms (43.62%), Ascaris suum (2.94%), Strongyloides ransomi (2.45%), and Trichuris suis (0.49%). No significant differences were observed in prevalence between the phases (p>0.05). Co-infections were also observed in sows in this study. The prevalence of nematode infections in sows remains relatively high; therefore, it is recommended to improve management practices, particularly on farms with wet housing conditions and irregular deworming schedules.